The art whisperer : an Alix London mystery - Elkins, Charlotte; Elkins, Aaron J. (Elkins, Charlotte. Alix London mystery., 2014)
When art conservator Alix London spots a forgery, she knows trouble will follow. So she's understandably apprehensive when her connoisseur's eye spots something off about a multimillion-dollar Jackson Pollock painting at Palm Springs's Brethwaite Museum--her current employer. Alix is already under fire, the object of a vicious online smear campaign. Now the Brethwaite's despicable senior curator, obsessed with the "maximization of monetized eyeballs," angrily refuses to decommission the celebrated Pollock piece. But it's only when a hooded intruder attacks Alix in her hotel room that the real trouble begins. And when FBI Special Agent Ted Ellesworth--with whom Alix had inadvertently, but thoroughly, botched a budding relationship just a year prior--turns up to investigate the Pollock, Alix knows she's about to have her hands full. In her third mystery, Alix London must see through mirages in the desert to uncover the knotted history of the painting--and save herself in the process.